Conductivity of Na5[MnCr(OH2)W11O39]·14H2O Treated by Chemically-Heated Diffusion of Er Permeation - Chen, Li-Qiang; Lin, Xiu-Mei; Liu, Li-Hong; Dai, Li-Mei; Zhu, Ming-Xia; Che, Wen-Shi; Tang, Jing (Asian Journal of Chemistry, 2014)
The gaseous permeation of erbium into the heteropoly compound Na5[MnCr(OH2)W11O39]·14H2O at 540 °C was performed. The studies of IR and XRD indicate that the keggin structure of the heteropoly compound is destroyed and the main product tungsten bronze Na0.54WO3 is obtained after permeation. ICP and XPS were used to determine the percentage composition of the erbium in the permeated sample. Conductivity of compounds before and after permeation were investigated by four-electrode method at room temperature and different measuring temperatures, the results reveal that the conductivity of the permeated compound is 105 times higher than that of the original compound at room temperature.